2019
DOI: 10.15275/rusomj.2019.0309
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of quality of life indicators associated with weight loss in patients with metabolically healthy obesity

Abstract: The purpose of the study was to analyse quality of life (QoL) indicators in patients with metabolically healthy obesity (MHO) associated with ≥ 5% weight loss. Material and Methods -The study involved 44 females with MHO (according to the IDF criteria of the metabolic syndrome (MS), 2005) and 33 females with metabolically unhealthy obesity (MUHO) aged 19-59 years. To assess QoL, we used the SF-36 questionnaire (Medical Outcomes Study -Short Form 36). Results -Initially QoL indicators in both groups were not si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 14 publications
0
1
1
Order By: Relevance
“…Vitality also has higher scores in MUO than MHO, supporting the better mental QoL of MUO. Most studies report a lower physical score in obesity in general, but contrary to our findings they report no statistical significance for the mental score [39][40][41]. On the other hand, Donini LM et al found no statistical significance for both physical and mental scores when comparing MHO and MUO [42] and Lopez-Garcia et al found similar MCS scores among all obesity phenotypes [43].…”
Section: Discussioncontrasting
confidence: 99%
“…Vitality also has higher scores in MUO than MHO, supporting the better mental QoL of MUO. Most studies report a lower physical score in obesity in general, but contrary to our findings they report no statistical significance for the mental score [39][40][41]. On the other hand, Donini LM et al found no statistical significance for both physical and mental scores when comparing MHO and MUO [42] and Lopez-Garcia et al found similar MCS scores among all obesity phenotypes [43].…”
Section: Discussioncontrasting
confidence: 99%
“…These ailments lead to disruption of circadian rhythms and, as a consequence, to changes in the melatonin production during the 24-hr day, a decrease in the quality of life, etc. [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%